High Power Auxiliary Converter for EMU with Permanent Magnet Traction Motor - WANG Jiajia; CHEN Xiang; TAN Miao; YAN YanJiao; LIU Changqing; LUO Dewei (Kongzhi Yu Xinxi Jishu)
It presented the main circuit, technical parameters and general structure of 270 kVA auxiliary converter for EMU with permanent magnet traction motor. Control methods for 4-quadrant rectifier and three-phase inverter of this auxiliary converter were mainly analyzed, and its performance was proved by tests. Practical running results show that this converter can meet the requirments of the EMU with permanent magnet traction motor.